the Correlation Study Between Accommodative Disorders and Asthenopia Among FKIK UKRIDA Students Class of 2024: Studi Korelasi Kelainan Akomodasi Dengan Astenopia Pada Mahasiswa FKIK UKRIDA Angkatan 2024 - Adiansyah, Adiansyah; Hudyono, Johannes; Simatupang, Aswin Oktavian Hasudungan (Jurnal MedScientiae, 2025)
Abstract Accommodation is the eye’s ability to adjust focus on objects at varying distances. Disorders in this function, such as accommodative insufficiency or excess, can cause visual symptoms like asthenopia (eye strain), commonly experienced by students involved in prolonged near work. Objective: This study aimed to determine the correlation between accommodative disorders and asthenopia among FKIK UKRIDA students, class of 2024. Methods: A descriptive-analytic study with a cross-sectional design was conducted involving 148 students selected through total sampling. Accommodative disorders were assessed using the RAF Rule following refraction, while asthenopia was measured using a standardized questionnaire. Data were analyzed using the Chi-Square test with a significance level of 0.05. Results: Of the 148 students, 89 (60.1%) had accommodative disorders, and 84 (56.8%) experienced asthenopia. Among those with accommodative disorders, 76 (85.4%) also reported asthenopia. The Chi-Square test showed a p-value of 0.000, indicating a statistically significant correlation between accommodative disorders and asthenopia. Conclusion: There is a significant correlation between accommodative disorders and asthenopia among FKIK UKRIDA students. Regular eye examinations and visual health education are recommended to prevent and manage visual discomfort in student populations.